Large dermoid cyst of the maxillofacial region: A case report and a review of the literature - Abubakar Mohammad Kaura; Bala Mujtaba; Sani Auwalu Balarabe; Bawa Anas Tsafe (Wolters Kluwer Medknow Publications, 2023)
Background: A dermoid cyst can be defined as a confined cavity that contains dermal adnexal structures, such as sebaceous glands, hair follicles, or sweat glands, with a distinct epithelial lining. A congenital dermoid cyst arises from the entrapment of pluripotential ectodermal cells along the lines of fusion between the first and second branchial arches during embryonic life. Case Report: This report presented the case of a 25-year-old woman who complained of a painless swelling on the floor of the mouth that had lasted for 6 years. An examination revealed ovoid submental swelling extending to the sublingual and submandibular spaces measuring 10 cm × 7 cm × 5 cm with intact skin. The swelling was soft, mobile, and non-tender upon palpation. Intraorally, it occupied the floor of the mouth and displaced the tongue superiorly. A yellowish crystalline aspirate was noted. Ultrasonography revealed a huge, thick-walled, deep-seated cystic mass showing florid mobile internal echoes and few separations on a turbid background with no intracystic solid components or calcification. A posterior-anterior view of the jaws revealed no bony involvement. Conclusion: A dermoid cyst can lead to difficulty in mastication, speech, respiration, and esthetic concerns if left untreated for a very long time. Early diagnosis and treatment can help prevent the occurrence of such complications. Despite, the late treatment in this case report, a successful treatment outcome was achieved.